Presence of glycoalkaloids in phloem of Solanum plants - Soulé, Silvia; Güntner, Carlos; Petersson, Carl; Ferreira, Fernando (Ciencia)
Solanum glycoalkaloids have been reported to play an important role in chemical defense against insects. However, their defensive role against phloem-feeding insects like aphids has been controversial. This study demonstrates the presence of -solanine and -chaconine ”“the two major potato glycoalkaloids”“ in the phloem of potato (Solanum tuberosum) and a wild relative (S. commersonii). These glycoalkaloids are also present in M. euphorbiae aphids reared on potato plants, demonstrating that these phloem-feeding insects do ingest these metabolites when reared on their host plants. These compounds are known to be toxic against many insect species, including aphids. The presence of glycoalkaloids in the phloem of Solanum plants and their ingestion by M. euphorbiae from their host plant phloem indicated the tolerance of this aphid specie to these metabolites and one or more detoxification mechanism may be involved.